THE INFLUENCE OF PROBLEM-BASED LEARNING MODELS ON THE CRITICAL THINKING ABILITY OF PHYSICS STUDENTS AT THE UNIVERSITY OF FLORES - Liu, An Nisaa Al Mu'min; Doa, Hamsa (JPF (Jurnal Pendidikan Fisika) FKIP UM Metro, 2023)
This research aims to determine the effect of problem based learning on the critical thinking abilities of physics students at the University of Flores. This type of research is experimental research with a research design that is pre-experimental design with a quantitative approach. The population of this study were all 17 students taking the introductory solid state physics course using a sampling technique, namely saturated side, where all members of the population were sampled. The results of the research show that there is an influence of the use of problem based learning on the critical thinking skills of physics students at the University of Flores. This is evidenced from the results of the analysis of the data obtained, namely the sig. (2-tailed) < 0.05 means Ho is rejected and H1 is accepted and is supported by t test calculations where the calculated t value > t table is obtained, namely 51.85 > 1.746.